2004
DOI: 10.1021/la0496892
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Environment on the Analysis of Phospholipids by Time-of-Flight Secondary Ion Mass Spectrometry

Abstract: Understanding the influence of molecular environment on phospholipids is important in time-of-flight secondary ion mass spectrometry (TOF-SIMS) studies of complex systems such as cellular membranes. Varying the molecular environment of model membrane Langmuir-Blodgett (LB) films is shown to affect the TOF-SIMS signal of the phospholipids in the films. The molecular environment of a LB film of dipalmitoylphosphatidylcholine (DPPC) is changed by varying the film density, varying the sample substrate, and the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…It is not possible in TOF-SIMS spectra or images to compare the concentrations of different analyte molecules, but the intensity will reflect relative concentrations of the same analyte molecule in the same image if the third issue, matrix effects, can be handled. Matrix effects means that the ionization of the analyte molecule will depend on the surrounding molecules (Sostarecz et al, 2004). Cryostat sectioning, causing ice crystal formation will equalize sodium and potassium levels in the samples so there is generally little reason to assume any drastic local variations in tissue chemistry that would cause the heterogeneous localization of fatty acids seen in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…It is not possible in TOF-SIMS spectra or images to compare the concentrations of different analyte molecules, but the intensity will reflect relative concentrations of the same analyte molecule in the same image if the third issue, matrix effects, can be handled. Matrix effects means that the ionization of the analyte molecule will depend on the surrounding molecules (Sostarecz et al, 2004). Cryostat sectioning, causing ice crystal formation will equalize sodium and potassium levels in the samples so there is generally little reason to assume any drastic local variations in tissue chemistry that would cause the heterogeneous localization of fatty acids seen in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…An increased yield of phosphocholine in the aqueous environment was explained by an increased probability of proton transfer from the surrounding water molecules as compared to the proton transfer from surrounding lipid molecules in the dry situation. Furthermore, Sostarecz et al 25,29 showed that the secondary ion yield of phosphocholine in DPPC LB films depends strongly on the substrate and on the presence of cholesterol (as a proton-donating surrounding molecule). A DPPC/CH LB film at a mole ratio of 2 : 1 forms a compressed, homogeneous liquid phase with a molecular area 30% lower than predicted for two noninteracting lipids.…”
Section: Model Systemsmentioning
confidence: 99%
“…Further, biological samples are often complex multi-component systems and are likely to cause complications in spectral interpretation due to matrix effects. For example, suppression/enhancement of signals from simple model lipid systems 46 implies that complications will arise in the analysis cell membranes, and it has been suggested that the localisation of drug molecules in tissue samples suffers from the same effect. 47 Interpretation of the data generated is also a consideration as the amount of data that can be generated using polyatomic projectiles, particularly from complex biological samples, can be overwhelming.…”
Section: Conclusion and Implications For Bio-analysismentioning
confidence: 99%